Mengidentifikasi Pembelajaran Berbasis Kemampuan Awal: Menyesuaikan Pengajaran Dengan Potensi Siswa - Anifa Wardah; Khofifah Dwi Wulandari; Shubhan Minan Nurirrohman; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
The initial ability of students is an important foundation in the learning process, because it determines the extent to which they can understand the material being taught. All students have initial abilities, which are the abilities they already have before they acquire certain terminal abilities. Initial ability indicates the current status of students' knowledge and skills towards the future status that the teacher wants students to achieve. To analyze students' initial abilities, at least an educator can identify learners' initial abilities by using techniques to detect initial abilities. Identifying learners' initial abilities allows teachers to design learning strategies that suit individual needs, so that learning can take place more effectively. In addition, educators can know well the different learning styles of students. Identifying students' initial abilities is an important step in the learning process. This article discusses four important indicators that educators can use to determine their students' initial skills. Initial skills are students' current level of knowledge and skills to achieve the future status that educators expect from students. Initial skills are the abilities that students already have before they acquire new final abilities. students who have equal initial skills can be brilliant or terrible at a subject, depending on their love or hate for that subject.